2022
DOI: 10.1200/jco.2022.40.16_suppl.4588
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of atezolizumab concurrent with radiotherapy in patients with muscle-invasive bladder cancer: An interim analysis of the ATEZOBLADDERPRESERVE phase II trial (SOGUG-2017-A-IEC(VEJ)-4).

Abstract: 4588 Background: Combined-modality treatments are bladder-preserving alternatives for patients (pts) who are not candidates for radical cystectomy by medical reasons, refusal, or patient´s choice. Immune therapies seem to potentiate tumor-specific immune response induced by radiotherapy (RT). Combination of RT with anti-PD-1/PD-L1 therapy appears safe and there are signs of promising activity. The aim of this study is to assess the efficacy and safety of atezolizumab (ATZ) concurrent with external beam radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another phase II study of durvalumab combined with concurrent RT for patients with a median age of 74 years, lymph node positivity, and an inability to undergo complete cystoscopic tumor resection, showed that the rate of CR was 50% (10 CR, 3 PR, 1 SD, and 6 PD), that of 1-year progression-free survival (PFS) was 73%, and that of 1-year and 2-year OS was 83.8% and 76.8%, respectively ( 21 ). A study of atezolizumab combined with radiotherapy for patients with a median age of 78.6 years showed that the pathologic complete remission (pCR) rate was 100% ( 22 ). Treatment with durvalumab and tremelimumab combined with radiotherapy for patients with MIBC also had a positive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Another phase II study of durvalumab combined with concurrent RT for patients with a median age of 74 years, lymph node positivity, and an inability to undergo complete cystoscopic tumor resection, showed that the rate of CR was 50% (10 CR, 3 PR, 1 SD, and 6 PD), that of 1-year progression-free survival (PFS) was 73%, and that of 1-year and 2-year OS was 83.8% and 76.8%, respectively ( 21 ). A study of atezolizumab combined with radiotherapy for patients with a median age of 78.6 years showed that the pathologic complete remission (pCR) rate was 100% ( 22 ). Treatment with durvalumab and tremelimumab combined with radiotherapy for patients with MIBC also had a positive effect.…”
Section: Discussionmentioning
confidence: 99%